Mother road [compact disc] - Potter, Grace, 1983- (Fantasy Records, 2023)
Composed over two years of driving back and forth on road trips across America, the new album from Grace Potter is an audacious and heart-pounding map of the soul. Produced by Eric Valentine (Queens of the Stone Age, Nickel Creek), It is Grace's fifth studio album and the follow-up to 2019's acclaimed, Grammy-nominated, Daylight. Featuring the singles 'Good Time,' and Ready Set Go.'